“Muara” A Musical Composition | ”Muara” Sebuah Komposisi Karawitan - Harys Arya Wibawa; I Wayan Rai S (Pusat Penerbitan LPPMPP ISI Denpasar, 2023)
Abstract An estuary is a place where river and sea water meet. One example of an estuary that inspires creators is the estuary at Ketewel Beach, Sukawati, Gianyar, Bali. Based on the inspiration from the estuary of Ketewel Beach, the creator made an innovative musical work entitled